KONSELING GESTALT DENGAN TERAPI SHOLAWAT THIBBIL QULLUB UNTUK MENGURANGI PENGGUNAAN OBAT TERLARANG PADA REMAJA DI DESA SILIRAGUNG BANYUWANGI - Ali Farhan, Zinedine (Jurnal Dakwah Tabligh, 2023)
The focus of this research is how the Process and Results of Islamic Counseling with Sholawat Thibbil Qullub Therapy reduce the use of prohibited drugs in adolescents in the village of Siliragung Banyuwangi. To answer the problems above, the researcher uses qualitative techniques in collecting data, using a comparison of the implementation process in the field and comparing the counselee’s condition before and after the process of implementing Islamic Counseling with Sholawat Thibbil Qullub Therapy to reduce the use of prohibited drugs in adolescents in Siliragung Village, Banyuwangi. In this study, it can be concluded that the use of illegal drugs occurs when the counselee experiences depression due to pressure from the Broken Home on his family. The main pressure from the counselee is that his mother has died, and the father of the counselee no longer cares for him, from this matter the counselee is unable to accept his life. In this study the counselor used Sholawat Thibbil Qullub Therapy so that the counselee could calm the heart so that he could get closer to Allah SWT. If the use is carried out in the long term, it is feared that it will result in side effects from the use of illegal drugs such as crystal meth, hyperthermia or overdose.